Psychology in action - Hyde, Margaret O.; Marks, Edward S.; Cather, Carolyn (New York : McGraw-Hill, 1967)
A survey of the many aspects of psychology as it attempts to understand human behavior through the study of learning, intelligence tests, prejudice and community relations, isolation, space travel, and animal behavior.
Bibliography: p. 154-157.
Keywords: Psychology -- Juvenile literature; Psychology -- Vocational guidance -- Juvenile literature; Psychology